Generation of Reactive Ketenes under Flow Conditions through Zinc-Mediated Dehalogenation - Hafner, Andreas; Ley, Steven V. (Synlett, 2015)
Herein, we describe the generation of highly reactive monoalkyl and phenyl ketenes by using a dehalogenation procedure under flow conditions. All ketenes were generated in good yields (determined by quenching with an appropriate aniline derivative) and showed high reactivity in the [2+2] cycloaddition with imines, resulting in the formation of a range of β-lactams at room temperature in less than 10 minutes. Furthermore, initial experiments were performed by using these reactive ketenes for the synthesis of β-lactams under flow conditions.
Keywords: ketenes; reactive intermediates; lactams; flow chemistry; cycloaddition